2007
DOI: 10.5713/ajas.2007.313
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Phylogenetic Analysis of the mtDNA D-loop Region in Tibetan Sheep

Abstract: Seventeen haplotypes were detected from the complete mitochondrial DNA control region sequences analyzed from eighty individuals of two Tibetan domestic sheep breeds. The nucleotide composition of all the sequences was 33.0% A, 29.7%T, 22.9%C and 14.4%G; G+C was 37.3%. The length of the sequences ranged from 1,107 bp to 1,259 bp. The difference between them was primarily due to 3-5 copy numbers of a 75 bp tandem repeat sequence. The NJ phylogenetic tree (the number of replications of bootstrap test is 1,000) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…4). Median-joining networks revealed that the most common parchment 'sheep' sequence matched (100% identity) only one individual from Tibet (GenBank accession DQ903201; Wang et al, 2007). Given its rarity, the Tibetan sequence is possibly the result of a numt or in situ DNA recombination (Lopez et al, 1996;Pä ä bo et al, 1990).…”
Section: Network Analysis Of Sequencesmentioning
confidence: 96%
“…4). Median-joining networks revealed that the most common parchment 'sheep' sequence matched (100% identity) only one individual from Tibet (GenBank accession DQ903201; Wang et al, 2007). Given its rarity, the Tibetan sequence is possibly the result of a numt or in situ DNA recombination (Lopez et al, 1996;Pä ä bo et al, 1990).…”
Section: Network Analysis Of Sequencesmentioning
confidence: 96%
“…Title: Distribution of haplotypes identified in the present study and in data available from GenBank. Description: The table provides distribution of haplotypes found in this study among previously studied contemporary sheep populations [2,57-63] available in GenBank.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…D-loop of two Tibetan sheep breeds was analyzed by Wang et al [83]. The length of the D-loop sequences varied considerably (between 1,107 bp and 1,259 bp) according to the copy numbers of a 75 bp tandem repeat located from 640 bp to 1,140 bp.…”
Section: Haplotype Diversitymentioning
confidence: 99%